THE PILATES EXERCISE IS MORE EFFECTIVE THAN CORE EXERCISE IN REDUCING NON-SPECIFIC LOW BACK PAIN FOR TAILORS IN DENPASAR CITY - Ratnasari, Ida Ayu Citra; Wahyuni, Nila; Artini, I Gusti Ayu (Majalah Ilmiah Fisioterapi Indonesia; Vol 5 No 1 (2017): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2017.v05.i01.p03, 2017)
ABSTRACT Low back pain bothers people both in their work life and social life. The aim of this research is to find out the effectiveness of Pilates exercise and Core exercise in decreasing the non-specific low back pain for tailors in Denpasar city. The research used experimental with pre and post two group design plan. The sample of the research was 24 people which were divided into two groups. Group treatment 1 was given Pilates Exercises and Group treatment 2 was given Core Exercise. The results of data analysis using a paired sample t-test for group one p = 0.000, for group two with p = 0.007. The results of data analysis using a Mann Whitney U-test which showed significant difference with result value of p = 0.000 (p < 0.05). From these results it can be concluded that the Pilates exercise is more effective in reducing non-specific low back pain than Core exercise. Keyword s : Low back pain, Pilates exercise, Core exercise,